Atrial adaptive rate pacing in sick sinus syndrome: effects on exercise capacity and arrhythmias. Issue 2 (February 1993) - Haywood, G A; Katritsis, D; Ward, J; Leigh-Jones, M; Ward, D E; Camm, A J
Abstract : OBJECTIVE--To test the hypotheses that adaptive rate atrial (AAIR) pacing: significantly increases maximal exercise capacity, and results in significant suppression of supraventricular and ventricular arrhythmia compared with fixed rate atrial (AAI) pacing. DESIGN--Prospective, randomised, single blind, crossover study with maximal treadmill exercise testing and 24 hour ambulatory electrocardiographic monitoring in AAIR and AAI modes. SETTING--Regional pacing centre. PATIENTS--30 consecutive patients (mean SD age 65 (12) years) with sick sinus syndrome who required permanent pacing, without evidence of conduction disturbance on 12 lead electrocardiograms or 24 hour ambulatory electrocardiographic monitoring and without other cardiovascular or systemic disease. INTERVENTIONS--Activity sensing or minute ventilation driven systems (AAI/AAIR) were implanted alternately. RESULTS--The mean (SD) peak heart rate in AAI mode was 122(28)v 130(22) in AAIR mode (p < 0.02) for the whole group and 104(17) v 120(5) (p < 0.003) for the patients with chronotropic incompetence. Exercise time was 12.3 (4.1) minutes in AAI and 12.3 (3.8) minutes in AAIR mode (NS) in the chronotropically incompetent patients. There were no significant differences in the Borg scores at peak exercise in AAI v AAIR mode in either group. The frequency per hour of atrial and ventricular arrhythmias showed no significant differences between the two modes in either the group as a whole or in the subgroups with chronotropic incompetence. CONCLUSION--AAIR pacing confers little benefit in sick sinus syndrome compared with AAI pacing.